2022
DOI: 10.1007/s44186-022-00046-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in leadership at breast surgical oncology fellowships

Abstract: Introduction Breast surgical oncology is a defined sub-specialty of general surgery that focuses on the surgical management of breast disease and malignancy within a multidisciplinary context. The fellowship directors (FD) that lead these programs have been selected for their abilities. As programs do research to ensure proper training for the next generation of breast surgical oncologists, we wanted to look into the FDs responsible for their training. Methods The Breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A Qualtrics survey was developed by the study team for dissemination to GYO PDs. Survey questions emphasized PDs’ demographic background, professional training, and involvement in various professional organizations ( Schachner et al, 2022 , Singh et al, 2021 , Wolbrom et al, 2021 , Madhan et al, 2022 , Donnally et al, 2020 , Choubey et al, 2022 ). Demographic information included age, gender, race, ethnicity, and sexual orientation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A Qualtrics survey was developed by the study team for dissemination to GYO PDs. Survey questions emphasized PDs’ demographic background, professional training, and involvement in various professional organizations ( Schachner et al, 2022 , Singh et al, 2021 , Wolbrom et al, 2021 , Madhan et al, 2022 , Donnally et al, 2020 , Choubey et al, 2022 ). Demographic information included age, gender, race, ethnicity, and sexual orientation.…”
Section: Methodsmentioning
confidence: 99%
“…Leadership trends within other surgical subspecialties, including breast surgery, cardiothoracic surgery, gastrointestinal surgery, hand surgery, spine surgery, and transplant surgery, have been published ( Schachner et al, 2022 , Singh et al, 2021 , Wolbrom et al, 2021 , Madhan et al, 2022 , Donnally et al, 2020 , Choubey et al, 2022 ). With the exception of breast surgical oncology, a specialty in which the majority of fellows are women, these studies reported that fellowship PDs are overwhelmingly male ( Schachner et al, 2022 , Singh et al, 2021 , Wolbrom et al, 2021 , Madhan et al, 2022 , Donnally et al, 2020 , Choubey et al, 2022 ). To date, there are no studies that have analyzed trends in leadership in obstetrics and gynecology (OB/GYN).…”
Section: Introductionmentioning
confidence: 99%